Government Bonds and Central Bank Assets in Global Crisis Mitigation Efforts in Indonesia - Seftarita, Chenny; Suriani; Ferayanti; Fitriyani; Diana, Asri (Department of Development Economics, Universitas Sriwijaya, 2025)
This study investigates the integrated effectiveness of government bonds and central bank assets within Indonesia's policy mix for mitigating global crises, an area often examined in isolation. Our primary objective is to quantify the short and long-run impacts of these instruments on Indonesia's economic growth during periods of global economic turbulence. Utilizing quarterly data spanning 2009 to 2021, we employ an Autoregressive Distributed Lag (ARDL) model. Empirical results reveal that both government bonds and central bank assets positively influence economic growth in both the short and long run. In the short run, these instruments are effective in stimulating economic activity and cushioning the immediate impacts of a global crisis. However, the long-run analysis indicates that while their supportive role persists, over-reliance, particularly through sustained fiscal deficits, can lead to a weakening of macroeconomic performance. Practical implications—prudent and balanced management of fiscal and monetary policies is essential to ensure long-term economic stability. Improving the quality of public spending is essential in strengthening debt governance, and encouraging close collaboration between fiscal and monetary authorities to optimize crisis mitigation strategies and promote sustainable growth.